Incidence and epidemiology of tibial shaft fractures. Issue 4 (April 2015) - Larsen, Peter; Elsoe, Rasmus; Hansen, Sandra Hope; Graven-Nielsen, Thomas; Laessoe, Uffe; Rasmussen, Sten
Abstract: Introduction: The literature lacks recent population-based epidemiology studies of the incidence, trauma mechanism and fracture classification of tibial shaft fractures. The purpose of this study was to provide up-to-date information on the incidence of tibial shaft fractures in a large and complete population and report the distribution of fracture classification, trauma mechanism and patient baseline demographics. Methods: Retrospective reviews of clinical and radiological records. Results: A total of 196 patients were treated for 198 tibial shaft fractures in the years 2009 and 2010. The mean age at time of fracture was 38.5 (21.2SD) years. The incidence of tibial shaft fracture was 16.9/100, 000/year. Males have the highest incidence of 21.5/100, 000/year and present with the highest frequency between the age of 10 and 20, whereas women have a frequency of 12.3/100, 000/year and have the highest frequency between the age of 30 and 40. AO-type 42-A1 was the most common fracture type, representing 34% of all tibial shaft fractures. The majority of tibial shaft fractures occur during walking, indoor activity and sports. The distribution among genders shows that males present a higher frequency of fractures while participating in sports activities and walking. Women present the highest frequency of fractures while walking and during indoor activities. Conclusion: This study shows an incidence of 16.9/100, 000/year for tibial shaft fractures. AO-type 42-A1 was the most common fracture type, representing 34% of all tibial shaft fractures.